Karapan Case in Islamic Perspective as a Madurary Cultural Identity in Pasean Pamekasan Community - Depict Pristine Adi; Siti Nor Farida (Islamika Inside: Jurnal Keislaman dan Humaniora, 2022)
Madura is an island located in the northeast of East Java. Madura has its own unique culture, one of the cultural icons in Madura is Karapan Sapi (Kerrabhân sapè), a cow racing competition. The Karapan Sapi culture emerged from the upbringing of K Ahmad Baidlowi, the grandson of Prince Pulang Jiwo (Panembbahan Blingi), to cultivate crops as a form of gratitude to God Almighty for the abundant harvest. But today's culture is experiencing degradation and is far from Islamic elements. This research is a literature study to see how the Karapan Sapi culture is from an Islamic perspective and its relation to the identity of the island of Madura itself. From the analysis of the existing theory, it can be concluded that Karapan Sapi (Kerrabhân sapè) is a typical Madurese tradition combining folk celebrations, entertainment, livestock health performances, and cattle racing. It is called Kerapan Sapi because two pairs of bulls compete for their running speed (é kerrap). Purpose if this research is to describe the karapan case in an Islamic perspective in the 20th century and the present. This research uses a qualitative approach with descriptive type. As for analysis used is qualitative data analysis which consists of three stages to answer the problem studied. The degradation in implementing the Kerapan Sapi tradition is due to criminal acts or activities that lead to things contrary to Islamic religious values. Torture of animals in the tradition of Karapan Sapi is the reason for the issuance of the Decree of the Governor of East Java No. 1/ins/2012 dated May 1, 2012, regarding the prohibition of bull racing with violence. The revitalization of Karapan Sapi's culture, which has a strong Islamic feel, takes time to implement. Law enforcement is also tricky and takes a long time to be realized. This is caused by the lack of firmness of the government and law enforcement, as well as the lack of awareness from the public.